Impact of Aedes aegypti V1016I and F1534C knockdown resistance genotypes on operational interventions - Alden S. Estep; Neil D. Sanscrainte; Muhammad Farooq; Keira J. Lucas; Rebecca L. Heinig; Edmund J. Norris; James J. Becnel (Scientific Reports)
Abstract Resistance to pyrethroids is common in Aedes aegypti populations. Mutations in the voltage gated sodium channel have an influence on the insecticide resistance (IR) phenotype. In much of the Western hemisphere, two of these knockdown resistance (kdr) mutations, V1016I and F1534C, result in six kdr genotype combinations in field populations. Strong pyrethroid IR and the failure of permethrin treated uniforms have been linked to the presence of the homozygous double kdr genotype (IICC) but the effects of the other five kdr combinations have not been rigorously examined, particularly with regard to operational efficacy. To better understand the impacts of these common kdr genotypes, we isolated three kdr haplotypes (VF, VC, & IC) from a field collected strain to produce six Ae. aegypti isoline strains with all the common V1016I/F1534C kdr genotypes. We then characterized the effects of these genotypes by CDC bottle bioassay and topical application and found increasing resistance to permethrin and deltamethrin as the number of IC haplotypes increased. Neither enzymatic activity nor malathion resistance increased with increasing pyrethroid resistance. We then assessed the operational impacts of these kdr genotypes. Field and wind tunnel spray of a pyrethrin formulation showed that even moderate resistance could significantly reduce knockdown and mortality. Studies with a synergized pyrethroid formulation showed effective recovery of mortality against all genotypes except for the IICC. In human bite studies, one or two IC haplotypes compromised the efficacy of permethrin treated fabrics. This study demonstrates that kdr mutations have distinct phenotypic effects in both the laboratory and operational interventions, and that the strength of pyrethroid resistance varies with the number of IC haplotypes present. Assessing kdr genotype is therefore critical for understanding IR in Ae. aegypti.